The Influence of Managers’ Personality Traits on Taking Project Risky Decisions - RASHID, AHMAD MAHMOUD MOHAMMAD (2017)
Several studies had explored the topic of individuals’ risk propensity related to general life domains such as: health, career, financial, safety and social. Yet, there is little research that was conducted specifically on project managers’ risk propensity related to project domains. The existing literature emphasizes the need for researchers to analyze individuals’ traits differences and its effects on shaping their risk propensity towards project success criteria. It is well understood that project managers’ will take their risky decisions based on available information and on their tendency to take risks, i.e. risk propensity. Therefore, this research investigated the influence of certain project managers’ personality traits on their risk propensity and risky decisions in relation to specific project success criteria. Accordingly, this research is expanding the existing literature on personality traits related to risk propensity, risk propensity in project management literature, individual characteristics related to project managers and project management success criteria. This research employed a mix of qualitative and quantitative methods to investigate the influence of 65 personality traits on project managers’ risky decisions in relation to project success criteria. Finally, the research examines the stability of project managers’ risk propensity across different project domains and in comparison to their general risk propensity.